Ocena sytuacji ekonomiczno-finansowej kluczowych podmiotów leczniczych województwa dolnośląskiego za lata 2012–2016 - Łagowski, Paweł (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The aim of the article is analysis of financial situation of hospitals which were founded by the Regional Government of Lower Silesia and now are owned by this institution. These analysed units represent a fundamental part of the provincial healthcare system. Understanding of their financial situation is crucial for improving whole healthcare system. The analysis used some indicators: of the assessment of liquidity, of the debt and of the profitability. Tendencies, noted in this paper, should be especially useful for medical management and for owners supervision.
Keywords: healthcare; financial analysis; medical entities